Discovery of Novel Approach for Regioselective Synthesis of Thioxotriaza-Spiro Derivatives via Oxalic Acid - Gopinatha, Vindya K.; Swarup, Hassan A.; Raghavan, Sathees C.; Mantelingu, Kempegowda; Rangappa, Kanchugarakoppal S. (Synlett, 2019)
A vital approach for the synthesis of a range of novel thioxotriaza-spiro derivatives is described. These new heterocyclic systems are obtained via oxalic acid catalyzed reaction of α,β-unsaturated ketones in the presence of 5,6-diamino-2-mercaptopyrimidine-4-ols; thus, spiro rings are constructed in one step. Notably, this transformation involves condensation of an amino group followed by enamine reaction with alkenes and subsequent reaction promoted by oxalic acid to afford spiro compounds with excellent regioselectivity.
Keywords: spiro rings; regioselective; oxalic acid; enamine; NHEJ